Excellent Local Government for Community Empowerment in the Region : A Case Study in Trenggalek Regency Indonesia - Rianto, Budi; Lestari, L. Tri; Sulistiyanto, Sulistiyanto (Universitas Padjadjaran, 2025)
The standard of regional autonomy in Indonesia continues; it’s because many community leaders still want the centralization of power based on the original Constitution of 1945, which is considered the form of the unitary state of the Republic of Indonesia. However, awareness of the importance of serving the community in the region to advance general welfare in the regional environment is still a dominant awareness even though in practice it cannot be separated from the ethnocentric interests and interests of power of community leaders in the region. The purpose of this study is to examine in depth the importance of excellent local government in advancing the welfare of the community. This research method is qualitative research, a case study in Trenggalek Regency, to obtain in-depth information about the implementation of autonomy in the region. The results of the study show that various changes in autonomy policies, especially since the enactment of Regulation number 23 of 2014, indicate a reduction in devolution in the regions, autonomy is more oriented as a public manager to provide excellent services to the community in the area in an economic perspective than autonomy in the political section.